UJI KELAYAKAN LIP BALM BERBASIS EKSTRAK BUAH MENTIMUN (CUCUMIS SATIVUS L.) DITINJAU DARI KARAKTERISTIK FISIK DAN STABILITAS - Fitria, Alfi Nur; Armandari, Mari Okatini; Ambarwati, Neneng Siti Silfi (Innovative: Journal Of Social Science Research, 2025)
Dry and chapped lips are a common problem caused by environmental factors such as extreme weather and UV exposure. The use of natural lip balm such as cucumber (Cucumis Sativus L.) which is rich in antioxidants and water content is a safe alternative to overcome this problem. The purpose of this study was to determine the feasibility of making lip balm based on cucumber (Cucumis Sativus L.) fruit extract in terms of its physical characteristics and stability. This research method was experimental. Cucumber fruit was macerated with virgin coconut oil (VCO) for 7 days. The results of the homogeneity test showed that the lip balm preparation was homogeneous with a pH of 5.07–7.30 which met SNI 16-4399-1996. The lip balm formulation obtained a spreadability of 3.23–3.53 cm and an adhesive strength of more than 10 seconds which indicated that the results had met the test requirements. However, the melting point test did not meet the test requirements with results of 47°C–48.5°C. In the stability test, there was no change in color, texture, aroma, and form of the preparation during the 28-day storage period with two temperature conditions of 25°C and 40°C. The conclusion of the results of this study shows that the formulation of cucumber fruit extract-based lip balm preparations meets the Indonesian National Standard (SNI) for lip balm preparations, both in terms of organoleptics, homogeneity, pH, and stability. However, the evaluation results show that the melting point of the preparation is still below the expected range, so it is necessary to optimize the composition of ingredients or manufacturing methods in future studies to increase the overall melting point.